An exploratory review of software agents - Ahmad A.; Ahmad M.S.; Yusoff M.Z.M. (2023)
Along with distributed problem solving and parallel artificial intelligence, agents and multi-agent systems collectively form one of the three broad areas which fall under distributed artificial intelligence (DAI). In this paper, we explore and review the general concepts of software agent technology; definitions, types, architectures, agent communication, multi-agent systems and agent development systems. 2008 IEEE.